Collocational Frequency and Context Effects on Idiom Processing in Advanced L2 Speakers. - Milburn, Evelyn; Vulchanova, Mila; Vulchanov, Valentin (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2021)
Multiword expressions have attracted attention recently following suggestions that they are acquired chunk-wise by children in the first language, while adults learning a second language may focus more on individual words within an expression. This is of particular interest for the acquisition of idioms, which are multiword expressions in which the literal meanings of the component words do not (always) directly contribute to overall phrasal meaning, resulting in a figurative interpretation. Figurative meaning access is speeded both by idiom-internal characteristics, like higher collocational frequency, and idiom-external characteristics, like supportive contexts. We examined the relationship between the collocational frequency of idioms' component words and the context in which an idiom is embedded. In a visual world eye-tracking study, advanced nonnative English speakers heard incomplete English phrases embedded within contexts that biased either literal or idiomatic continuations and saw images representing literal or figurative completions, or distractor images. Participants showed higher looks to figurative completions that were at odds with contextual bias, suggesting that integrating frequency information in context in adult L2 users may be overridden when a phrase is figurative. However, higher-proficiency participants showed more successful suppression of inappropriate figurative continuations. These results suggest that idiom conventionality when compared to literal phrases may be a stronger driver of predictive looks than collocational frequency or contextual bias alone, and that sensitivity to contextual fit when processing idioms may still be developing even among very advanced L2 users.